Affective Science Perspectives on Cancer Control: Strategically Crafting a Mutually Beneficial Research Agenda. (May 2015) - Ferrer, Rebecca A.; Green, Paige A.; Barrett, Lisa Feldman
Cancer control research involves the conduct of basic and applied behavioral and social sciences to reduce cancer incidence, morbidity, and mortality and improve quality of life. Given the importance of behavior in cancer control, fundamental research is necessary to identify psychological mechanisms underlying cancer risk, prevention, and management behaviors. Cancer prevention, diagnosis, and treatment are often emotionally laden. As such, affective science research to elucidate questions related to the basic phenomenological nature of emotion, stress, and mood is necessary to understand how cancer control can be hindered or facilitated by emotional experiences. To date, the intersection of basic affective science research and cancer control remains largely unexplored. The goal of this article is to outline key questions in the cancer control research domain that provide an ecologically valid context for new affective science discoveries. We also provide examples of ways in which basic affective discoveries could inform future cancer prevention and control research. These examples are not meant to be exhaustive or prescriptive but instead are offered to generate creative thought about the promise of a cancer research context for answering basic affective science questions. Together, these examples provide a compelling argument for fostering collaborations between affective and cancer control scientists.